Case report on splenic abscess with pleural effusion caused by enteric fever - Shaji, Shiby Sara; George, Shone Padinjarethil; Varughese, Mohan; Abraham, Thomas Jacob (International Journal of Basic & Clinical Pharmacology, 2023)
Splenic abscess is an infrequent complication of enteric fever caused by Salmonella typhi. The incidence rate ranges from 0.14-2%. Clinical manifestations are often nonspecific and may be presented as fever with left upper quadrant abdominal pain and a palpable tender mass. Diagnosis is often difficult and splenic abscess management is based on surgical interventions and antibiotic therapy. In this case report we would like to highlight splenic abscess with left reactive pleural effusion as a rare complication of Salmonella typhi infection.